Thermoplastic Starch Composites With Titanium Dioxide and Vancomycin Antibiotic: Preparation, Morphology, Thermomechanical Properties, and Antimicrobial Susceptibility Testing - Ujcic, Aleksandra; Krejcikova, Sabina; Nevoralova, Martina; Zhigunov, Alexander; Dybal, Jiri; Krulis, Zdenek; Fulin, Petr; Nyc, Otakar; Slouf, Miroslav (Frontiers in Materials, 2020)
Biodegradable composites of thermoplastic starch (TPS), titanium dioxide particles (TiO2; average size 0.2 μm), and/or antibiotic (ATB; vancomycin) were prepared. Light and electron microscopy demonstrated that our recently developed, two-step preparation procedure yielded highly homogeneous TPS matrix with well-dispersed TiO2 particles even for high filler concentrations (up to 20%). Oscillatory shear rheometry showed an increase in viscosity of TPS after addition of TiO2 and ATB (from ca 2 × 105 Pa·s to ca 1 × 106 Pa·s at 1 rad/s and 120°C). However, the high viscosity of TPS/TiO2/ATB composites did not prevent reproducible preparation of the composites by melt-mixing. Dynamic mechanical analysis proved a significant increase in shear moduli (storage, loss and complex modulus) of TPS after addition of TiO2 and ATB (storage modulus increased from ca 25 MPa to more than 600 MPa at 1.33 rad/s at room temperature). Both rheological and mechanical properties indicated strong interactions among TPS matrix, filler, and antibiotics. The final TPS composites were soft enough to be cut with a sharp blade at room temperature, the TPS matrix was fully biodegradable, the TiO2 filler was biocompatible, and the ATB could be released locally during the matrix degradation. Selected samples were tested for bacterial susceptibility using standard tube dilution test and disk diffusion test. The results proved that the ATB retained its bacteriostatic properties after the thermal processing of the composites. Therefore, the prepared TPS/TiO2/ATB composites represent a promising material for biomedical applications related to the local release of antibiotics.